PERBEDAAN PERSEPSI ETIS MAHASISWA AKUNTANSI TERHADAP PRAKTIK EARNINGS MANAGEMENT - Martin Martin; Nurmala Ahmar (Universitas Brawijaya, 2010)
This study investigates whether gender influences accounting students' perceptions of earnings management. Earnings management is the practice of making discretionary accounting choices or timing operating decisions to move reported earnings toward a desired goal. In this research, earning management has 4 four indicators: type of manipulation, direction of manipulation, materiality, and intention. Prior research reveals wide disagreement among both students and business executives regarding the ethical acceptability of earnings management. Male and female accounting students from Surabaya were evaluated using thirteen items that indicate and describe earnings management practices. No differences were detected between the responses of the male and female students or between the working and non-working students. The result shows that the practice of earnings management is perceived similarly in all groups of students studied.